The Compound Heatwave and Drought Event in the Summer of 2022 and the Impacts on the Power System in Southwest China - Changyi Liu; Bo Lu; Jie Liu; Fang Yang; Han Jiang; Zhiyuan Ma; Qing Liu; Jiangtao Li; Wenkai Liu (Energies)
An unprecedented compound heatwave and drought (CHD) event occurred in the summer of 2022 in Southwest China. This extreme climate event posed significant challenges to the power system and highlights the importance of disaster risk management and adaptation to extreme climate events in the power sector. This paper assesses the complementary effects of variations in hydropower, wind, solar power generation and the power load gap in response to this CHD event. The CHD resulted in a remarkable 50% decrease in hydropower generation during the summer of 2022. Similarly, wind speeds in the southwest region slightly decreased from 2.0 m/s in mid-July to 1.7 m/s in early August. On the contrary, solar power generation doubled from mid-July to mid-August. In the summer of 2022, the increase in solar power generation could not compensate for the gap between the dramatically increased cooling demand and the reduced hydropower output. Nevertheless, it highlighted the potential synergy of power source grid load storage and hydro–wind–solar power combinations in addressing future CHD events, and the importance of early-warning for extreme climate events in the new-type power system in the future.